Peran Pelatihan dan Pengembangan SDM dalam Membangun Budaya Pelayanan Prima di Bank Konvensional - Cahyo Rachmat Irawan; Bergin Abisal Putra (Draf Solusi Indonesia, 2024)
This study aims to analyze the role of training and human resource development in fostering a culture of service excellence in conventional banks. Providing outstanding service is crucial for maintaining customer satisfaction and loyalty in the highly competitive banking industry. Through structured training programs and continuous employee development, banks can enhance their workforce's competencies in delivering efficient and satisfactory services. Well-trained employees can not only handle tasks proficiently but also adapt to evolving customer needs and technological advancements. By investing in training and human resource development, banks can improve service quality, strengthen their competitive edge, and cultivate an organizational culture centered around service excellence, ultimately boosting customer satisfaction and bank reputation.